Do intronic mutations affecting splicing of WT1 exon 9 cause Frasier syndrome?. Issue 1 (January 1998) - Kikuchi, H; Takata, A; Akasaka, Y; Fukuzawa, R; Yoneyama, H; Kurosawa, Y; Honda, M; Kamiyama, Y; Hata, J
Abstract : The WT1 gene, one of the genes responsible for Wilms tumour, is thought to play a crucial role in the development of the kidneys and gonads. This gene encodes four protein isoforms resulting from two alternative splicing sites, one of which involves inclusion or exclusion of lysine, threonine, and serine (KTS) between the third and fourth zinc finger domains. WT1 is virtually always mutationally inactivated in patients with Denys-Drash syndrome. We analysed WT1 in eight patients who had been diagnosed as having this syndrome, and identified five previously unknown mutations affecting splicing donor sites of intron 9. These mutations affect alternative splicing. The isoforms retaining KTS are not produced. The clinical features of the patients with these intronic mutations were consistent with those of Frasier syndrome, characterised by a more slowly progressive nephropathy than Denys-Drash syndrome, associated streak gonads, and no Wilms tumour development. Our results indicate that WT1 isoforms, including/excluding KTS, have different functions in tumorigenesis and organogenesis of the kidneys and gonads.